2019
DOI: 10.1080/14756366.2019.1611801
|View full text |Cite
|
Sign up to set email alerts
|

Fibrate-basedN-acylsulphonamides targeting carbonic anhydrases: synthesis, biochemical evaluation, and docking studies

Abstract: A large library of fibrate-based N-acylsulphonamides was designed, synthesised, and fully characterised in order to propose them as zinc binders for the inhibition of human carbonic anhydrase (hCA) enzymatic activity. Synthesised compounds were tested against four hCAs (I, II, IX, and XII) revealing a promising submicromolar inhibitory activity characterised by an isozyme selectivity pattern. Structural modifications explored within this scaffold are: presence of an aryl ring on the sulphonamide, p-substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…1A). 15,16 Interestingly, several potent antiviral agents carrying an N-acylsulfonamide group and targeting the NS3 or NS3-4A protease of hepatitis C virus have also been described. [17][18][19] Recently, our group reported the synthesis of 5′-N-sulfonamide adenosine derivatives that showed significant inhibition of SARS-CoV-2 (N7-guanine)-methyltransferase (N7-MTase) nsp14 by acting as a competitor of S-adenosyl-L-methionine (SAM), the methyl donor in the N7-cap RNA methylation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A). 15,16 Interestingly, several potent antiviral agents carrying an N-acylsulfonamide group and targeting the NS3 or NS3-4A protease of hepatitis C virus have also been described. [17][18][19] Recently, our group reported the synthesis of 5′-N-sulfonamide adenosine derivatives that showed significant inhibition of SARS-CoV-2 (N7-guanine)-methyltransferase (N7-MTase) nsp14 by acting as a competitor of S-adenosyl-L-methionine (SAM), the methyl donor in the N7-cap RNA methylation.…”
mentioning
confidence: 99%
“…1A). 15,16 Interestingly, several potent antiviral agents carrying an N -acylsulfonamide group and targeting the NS3 or NS3-4A protease of hepatitis C virus have also been described. 17–19…”
mentioning
confidence: 99%
“…Primary sulfonamides are a broad class of specific inhibitors of CA enzymes. 39 Secondary sulfonamides are generally regarded as weak CAIs. However, they have historically been an important class.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…34 Aromatic/heterocyclic sulfonamides, which are of great importance in the pharmaceutical industry, have been extensively used for many years to investigate the pathophysiology and treat diverse diseases such as epilepsy, antibacterial, glaucoma, antibacterial, anticancer, antifungal, anti-obesity, diuretic, antiglaucoma and anticonvulsant. [35][36][37] Furthermore, secondary sulfonamides and their N-substituted forms [38][39] have been identified as potent inhibitors of hCA I and hCA II in most studies, whereas some bis-sulfonamide compounds have been reported to be potent inhibitors against CA II isozyme and less inhibitory against CA I. 40 Recently, molecular hybridization design has emerged as a new approach by combining at least two pharmacophore-specific moieties to modulate multiple disease targets simultaneously, which will be the combined force in providing pharmacological activity and will also increase the capacity to interact with multiple biological targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation